2021
DOI: 10.1186/s12951-021-00947-9
|View full text |Cite
|
Sign up to set email alerts
|

Amplified antitumor efficacy by a targeted drug retention and chemosensitization strategy-based “combo” nanoagent together with PD-L1 blockade in reversing multidrug resistance

Abstract: Background Recent studies have demonstrated that multidrug resistance (MDR) is a critical factor in the low efficacy of cancer chemotherapy. The main mechanism of MDR arises from the overexpression of P-glycoprotein (P-gp), which actively enhances drug efflux and limits the effectiveness of chemotherapeutic agents. Results In this study, we fabricated a “combo” nanoagent equipping with triple synergistic strategies for enhancing antitumor efficacy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…5A and C). 34 These results suggested that L@S/L has a strong potential for tumor accumulation via the EPR effect.…”
Section: Resultsmentioning
confidence: 87%
“…5A and C). 34 These results suggested that L@S/L has a strong potential for tumor accumulation via the EPR effect.…”
Section: Resultsmentioning
confidence: 87%
“…This indicated that TMZ/siPD-L1@GLPN/dsb and TMZ/siPD-L1@LPN/dsb escaped from the endosome/lysosome, which reduced the enzymatic degradation of siPD-L1 in endosome/lysosomes. Many cationic polymers such as PEI are used to help siRNA-PEI electrostatic complex escape from endosomes through the proton sponge mechanism . Besides, DOPE, a noncationic helper lipid, is often used to facilitate endosomal escape of lipid-based siRNA delivery systems .…”
Section: Resultsmentioning
confidence: 99%
“…Many cationic polymers such as PEI are used to help siRNA-PEI electrostatic complex escape from endosomes through the proton sponge mechanism. 45 Besides, DOPE, a noncationic helper lipid, is often used to facilitate endosomal escape of lipid-based siRNA delivery systems. 46 Thus, PEI and DOPE were important components in TMZ/siPD-L1@GLPN/dsb, Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Among those organic photosensitizers, special attention was paid to the porphyrin derivative TCPP [TCPP = tetrakis (4-carboxyphenyl) porphyrin] due to its merits of fluorescence imaging and PDT effect [11,12]. The appropriate proportion of metal ions and TCPP can result in the reasonable force between the metal ions and carboxylate groups to disrupt the π-π stacking of the free TCPP ligands and form NMOFs with good biological and light stability [13,14].…”
Section: Introductionmentioning
confidence: 99%